Measurement of upsilon production in 7 TeV pp collisions at ATLAS - Anduaga, Xabier Sebastián (2013)
Using 1.8 fb−1 of -pp collisions at a center-of-mass energy of 7 TeV recorded by the ATLAS detector at the Large Hadron Collider, we present measurements of the production cross sections of Υ(1S,2S,3S) mesons.Υmesons are reconstructed using the di-muon decay mode. Total production cross sections for pT <70 GeV and in the rapidity interval |yΥ| <2.25 are measured to be 8.01±0.02±0.36±0.31 nb, 2.05±0.01±0.12±0.08 nb, 0.92±0.01±0.07±0.04 nb, respectively, with uncertainties separated into statistical, systematic, and luminosity measurement effects. In addition, differential cross section times di-muon branching fractions forΥ(1S),Υ(2S), and Υ(3S)as a function of Υ transverse momentum pT and rapidity are presented. These cross-sections are obtained assuming unpolarized production. If the production polarization is fully transverse or longitudinal with no azimuthal dependence in the helicity frame the cross-section may vary by approximately ±20%.If a non-trivial azimuthal dependence is considered, integrated cross-sections may be significantly enhanced by a factor of two or more. We compare our results to several theoretical models of Υ meson production, finding that none provide an accurate description of our data over the full range of Υ transverse momenta accessible with this dataset.